2009
DOI: 10.1177/0363546509340771
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Delay of the Knee Flexor Muscles Is Impaired After Harvesting Hamstring Tendons for Anterior Cruciate Ligament Reconstruction

Abstract: The results showed that harvesting the semitendinosus and gracilis tendons for anterior cruciate ligament reconstruction significantly increased the electromechanical delay of the knee flexors. Increased hamstring electromechanical delay might impair knee safety and performance by modifying the transfer time of muscle tension to the tibia and therefore affecting muscle response during sudden movements in athletic activities. However, further investigation is required to identify whether the increased electrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
1
41
0
1
Order By: Relevance
“…5 In addition, the duration of EMD is dependent on the mechanical properties of tendon structures. 24 It is speculated that a decrease in stiffness of tendon structures, which means a decrease in the ability to transmit muscle force, plays an important role in increasing the duration of the EMD. Therefore, a longitudinal prospective study would be potentially useful to assess the clinical and pathological factors leading to these changes in individuals with PFPS.…”
Section: Discussion Tmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In addition, the duration of EMD is dependent on the mechanical properties of tendon structures. 24 It is speculated that a decrease in stiffness of tendon structures, which means a decrease in the ability to transmit muscle force, plays an important role in increasing the duration of the EMD. Therefore, a longitudinal prospective study would be potentially useful to assess the clinical and pathological factors leading to these changes in individuals with PFPS.…”
Section: Discussion Tmentioning
confidence: 99%
“…24 Several researchers have reported that EMD is a component of protective reflexes and is related to athletic performance. 9,25,27 The shorter the EMD, the faster the muscle force transmission and the better the performance and protective reflex.…”
mentioning
confidence: 99%
“…EMD represents a series of complex processes of converting an electrical stimulus to a mechanical response, thus being affected by several factors such as fatigue (38,39), age (12,38), contraction modality (6,14,40), muscle-tendon strain (23), myotonic dystrophy (26), and tendon harvesting (30). Previous studies have taken a variety of approach for measuring EMD and sometimes used different tenninology such as force time (37) and total response time (40) to refer to the time lag between the onset of electrical activity (or electrical stimulus) and the beginning of force (or torque) development.…”
Section: Discussionmentioning
confidence: 99%
“…Before explosive movements like jumping, landing, running, and cutting the involved lower limb muscles are innervated before ground contact in order to build up necessary force before the impact, and in consideration to the electromechanical delay (EMD) (Viitasalo and Bosco, 1982;Dyhre-Poulsen and Laursen, 1984;Aura and Komi, 1986;Gollhofer and Kyrolainen, 1991). Recent studies have shown hamstring EMDs of approximately 100 ms (Ristanis et al, 2009;Troy Blackburn et al, 2009), but no differences between males and females were observed (Troy Blackburn et al, 2009). Thus, lower hamstring activation found during 50 ms prior to initial ground contact in this study indicates lower hamstring force in the first part of ground contact for the female subjects.…”
Section: Discussionmentioning
confidence: 99%